131PCabozantinib in Asian patients with hepatocellular carcinoma and other solid tumours: Population pharmacokinetics analysis. (24th November 2019) - Hsu, C-H; Nguyen, L; Cheng, A-L; Nguyen, T X Q; Brendel, K; Aslanis, V; Benzaghou, F
Abstract: Background: Cabozantinib, an inhibitor of MET, AXL and VEGF receptors, was recently approved for the treatment of patients with advanced hepatocellular carcinoma (HCC) who had previously received sorafenib, based on findings of the CELESTIAL trial. We previously reported cabozantinib pharmacokinetics (PK) data based on 9 cabozantinib studies (N = 1534), Here, we report updated cabozantinib PK data in Asian and non-Asian ethnicities including patients with HCC. Methods: We used data from ten cabozantinib studies that included healthy volunteers (HV) and patients with various cancer types (HCC, renal cell carcinoma, castration-resistant prostate cancer, medullary thyroid cancer [MTC], and glioblastoma multiforme). Studies pertinent to HCC were the CELESTIAL trial (NCT01908426) and the HCC cohort of a phase 2 trial (NCT00940225). The impact on PK parameters of selected covariates (age, weight, sex, race, cancer type, formulation, and liver dysfunction according to the National Cancer Institute Organ Dysfunction Working Group [NCI-ODWG]) was evaluated. Steady-state PK parameters were predicted for Asian and non-Asian patients. Results: Data from 2023 individuals were included (cancer patients, n = 1883; HV, n = 140), of whom 211 were of Asian ethnicity and 1812 of non-Asian ethnicity. MTC cancer type had the largest effect on cabozantinib PK parameters, with a 90% increase in apparent clearance (CL/F) relative to HV. Other cancer types, including HCC, and liver dysfunction per NCI-ODWG did not impact cabozantinib PK. However, because CELESTIAL excluded patients with Child-Pugh scores of B or C, results on patients with more compromised liver function are limited. A 24% decrease in CL/F was observed in females; Asian ethnicity, age, and weight had no clinically significant impact on cabozantinib clearance. Conclusions: Minimal cabozantinib PK and predicted exposure differences were observed across various cancer types except for MTC. The PK of cabozantinib was similar in individuals of Asian and non-Asian ethnicity. These findings are consistent with the major metabolic pathway of cabozantinib via cytochrome P450 3A4 which is not prone to genetic polymorphism. Editorial acknowledgement: The authors thank Isabelle Kaufmann, PhD of Oxford PharmaGenesis, Oxford, UK for providing medical writing support, which was sponsored by Ipsen, Abingdon, UK in accordance with Good Publication Practice guidelines. Legal entity responsible for the study: Ipsen. Funding: Ipsen. Disclosure: C-H. Hsu: Research grant/Funding (self): Ipsen; Honoraria (self): Ipsen. L. Nguyen: Full / Part-time employment: Exelixis. A-L. Cheng: Honoraria (self): Bayer; Honoraria (self): Eisai; Honoraria (self): Merck Sharp Dohme; Honoraria (self): Merck Serono; Honoraria (self): Novartis; Honoraria (self): Ono Pharmaceutical; Honoraria (self): Roche/Genentech; Honoraria (self): IQVIA. Advisory/Consultancy: Bayer Schering Pharma; Advisory/Consultancy: Bristol-Myers Squibb; Advisory/Consultancy: Eisai; Advisory/Consultancy: Merck Serono; Advisory/Consultancy: Novartis; Advisory/Consultancy: Ono Pharmaceutical; Advisory/Consultancy: Exelixis; Advisory/Consultancy: Nucleix Ltd.; Advisory/Consultancy: Roche/Genentech; Advisory/Consultancy: IQVIA. Speaker Bureau/Expert testimony: Bayer Yakuhin, Ltd.; Speaker Bureau/Expert testimony: Novartis; Speaker Bureau/Expert testimony: Eisai; Speaker Bureau/Expert testimony: Ono Pharmaceutical; Speaker Bureau/Expert testimony: Amgen Taiwan. Travel/Accommodation/Expenses: Bayer Yakuhin, Ltd.; Travel/Accommodation/Expenses: Novartis; Travel/Accommodation/Expenses: Eisai; Travel/Accommodation/Expenses: Ono Pharmaceutical; Travel/Accommodation/Expenses: Roche/Genentech; Travel/Accommodation/Expenses: IQVIA. T.X.Q. Nguyen: Full / Part-time employment: Ipsen. K. Brendel: Full / Part-time employment: Ipsen. V. Aslanis: Full / Part-time employment: Ipsen. F. Benzaghou: Full / Part-time employment: Ipsen.